AKTUALISASI NILAI PANCASILA MELALUI PELAYANAN MASYARAKAT DI LINGKUP BALAI PRODUKSI INDUK UDANG UNGGUL DAN KEKERANGAN (BPIU2K) KARANGASEM, BALI - Juliana, Fita; Ningrum, Rema Apria; Hasna, Nurul; Helmiana, Baiq; Rasuliyanasari , Maviroh; Diniarti, Nanda (Universitas Mataram, 2023)
In the era of increasingly interconnected digital technology, the utilization of gadgets has become inseparable from daily life. However, this has also resulted in a decline in social interaction and community participation, as well as the neglect of Pancasila values. This research delves into how Pancasila values can be actualized in everyday life, particularly within the influence of gadgets. Through a Kuliah Kerja Nyata (KKN) at BPIU2K Karangasem, Bali, efforts were made to actualize Pancasila values through engagement in community activities amidst the impact of gadgets. The methodology involved location surveys and the execution of activities such as environmental clean-up, religious practices, computer guidance, and health assessments. Through these activities, Pancasila values such as mutual cooperation, responsibility, and unity are emphasized. Study sessions and communal meals strengthen social bonds and religious awareness. Computer guidance and health assessments also support the improvement of community well-being. Additionally, blood donation and health checks aid in disease prevention and bolster the spirit of unity. Through this approach, it is anticipated that Pancasila values remain pertinent in the digital era, nurturing social responsibility, and fostering collective consciousness within society.